Complete mitochondrial genomes of Baikal oilfishes (Perciformes: Cottoidei), earth’s deepest-swimming freshwater fishes - Michael W. Sandel; Andres Aguilar; Kayla Fast; Stephen O’Brien; Alla Lapidus; David B. Allison; Veronika Teterina; Sergei Kirilchik (Mitochondrial DNA. Part B. Resources, 2017)
Sculpins are predominantly benthic sit-and-wait predators that inhabit marine and freshwaters of the Northern Hemisphere. In striking contrast to riverine relatives, sculpins endemic to Lake Baikal have diversified in both form and function, with multiple taxa having adaptations for pelagic and bathyal niches within the world’s deepest lake. Baikal Oilfishes (Comephorus spp.) represent a highly apomorphic taxon with unique skeletal morphology, soft anatomy, and reproductive ecology. Selection for novel behavior and life history may be evident in genes responsible for organismal energy balance, including those encoding subunits of the electron transport chain. Complete mitochondrial genomes were sequenced for the Big Baikal Oilfish (Comephorus baicalensis) and Little Baikal Oilfish (Comephorus dybowskii). Mitochondrial genomes encode genes essential for electron transport, and data provided here will complement ongoing investigations of genome-to-phenome maps for teleost respiration and metabolism. Phylogenetic analyses including oilfish mitogenomes and all publicly available cottoid representative sequences are largely concordant with previous studies.